2016
DOI: 10.1103/physrevb.94.180503
|View full text |Cite
|
Sign up to set email alerts
|

Granular superconductivity and magnetic-field-driven recovery of macroscopic coherence in a cuprate/manganite multilayer

Abstract: We show that in Pr 0.5 La 0.2 Ca 0.3 MnO 3 /YBa 2 Cu 3 O 7 (PLCMO/YBCO) multilayers the low temperature state of YBCO is very resistive and resembles that of a granular superconductor or a frustrated Josephson-junction network. Notably, a coherent superconducting response can be restored with a large magnetic field which also suppresses the charge-orbital order in PLCMO. This coincidence suggests that the granular superconducting state of YBCO is induced by the charge-orbital order of PLCMO. The coupling mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…Instead, there exists evidence for a granular superconducting state with grains that are strongly superconducting and boundaries at which the macroscopic coherence of the superconducting wave function is broken. A terahertz spectroscopy study in zero magnetic field has indeed revealed a strong plasmonic mode at nonzero frequency that develops below 80 K and arises from a strongly confined superconducting condensate [36].…”
Section: The Insulating Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, there exists evidence for a granular superconducting state with grains that are strongly superconducting and boundaries at which the macroscopic coherence of the superconducting wave function is broken. A terahertz spectroscopy study in zero magnetic field has indeed revealed a strong plasmonic mode at nonzero frequency that develops below 80 K and arises from a strongly confined superconducting condensate [36].…”
Section: The Insulating Andmentioning
confidence: 99%
“…084801-3 Figure 1(a) recalls the R-T curves in zero magnetic field (blue line) and at 9 T (red line) of a PLCMO(20 nm)/YBCO(7 nm)/PLCMO(20 nm) (PYP) trilayer from Ref. [36]. These were interpreted in terms of a transition from a granular superconducting state with a Coulomb blockade at zero field to a macroscopically coherent superconducting one with T c ≈ 75 K at 9 T.…”
Section: Multilayers Consisting Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Large MR has also been observed in several inhomogeneous or disordered materials that exhibit a superconductor-insulator transition 21,22 as e.g. thin amorphous or granular metallic films on insulators, [23][24][25][26] fractal Pb films on silicon, 27 Pb-Si hetorojunctions, 28 amorphous metal-metalloid films, [29][30][31][32][33] cuprate superconductors [34][35][36][37][38] and heavily doped semiconductors. [39][40][41][42][43] There has been an academic debate about the nature of this phase transition and the origin of the large negative MR. 12,[44][45][46] Some theories consider a global quantum phase transition 21,33,47,48 or quantum corrections to the classical magnetotransport.…”
Section: R(b)−r(0) R(0) R (B) > R (0) Positive Mr R(b)−r(0) R(b)mentioning
confidence: 99%